A disturbance in the force : how the Star Wars holiday special happened [videorecording (DVD)] - Smith, Kevin, 1970-; Green, Seth, 1974-; Scheer, Paul, 1976-; Oswalt, Patton, 1969- (Giant Pictures, 2023)
A documentary film chronicling the making of and the legacy of the television special "Star Wars Holiday Special", originally aired on CBS television network the week before Thanksgiving 1978.